Modeling environmental interactions and collaborative interventions for childhood stunting: A case from Indonesia - Sri Juni Woro Astuti; Sayekti Suindyah Dwiningwarni; Suryo Atmojo (Dialogues in Health)
Child stunting is a significant problem in Indonesia and requires special attention even though the government has implemented various programs to overcome it. The formulation of this study is: 1) How is the management of stunting handling based on the government's perspective? 2) What is the role of parties involved in the prevention and handling of stunting? 3) What is an effective stunting management model? The objectives of this research are: 1) The implementation of local government stunting handling policies; 2) Analyze cross-sector collaboration and active participation of all stakeholders; and 3) Formulate an integrated model for handling stunting and the implementation of system synergy. The design of this study uses a qualitative approach with a phenomenological which was carried out in the period from January 2023 to September 2024 in Indonesia. The informants interviewed in this study were 60 people recruited using the purposive sampling method also involving Focus Group Discussions (FGD). The results of this study identify that the success of stunting reduction efforts depends on effective collaboration between various stakeholders. The study highlights that social capital, which consists of social networks, collective norms, and trusts, plays an important role in strengthening stunting reduction efforts. Further research is needed to explore the specific impacts of social capital in other contexts in Indonesia and to develop more adaptive intervention models to local social and cultural dynamics.